THE PHILOSOPHY OF POWER RELATIONSHIP IN POSTMODERN PERIOD - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analyses the postmodern model of power, its philosophical basis and specific features.